NEPOTISME DALAM PERSPEKTIF HUKUM PIDANA INDONESIA (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Nepotism is any act of the conduct of the state against the law that benefits the interests of his family and / or cronies above the interests of the community, nation and state. The practice of nepotism is still frequently practiced in Indonesia, it has even become a public secret in the process of recruiting new employees, both in government agencies and companies and in the private sector. Nepotism is regulated in Act Number 28 of 1999 concerning Organizers that are Clean, Corruption-Free, Collusion and Nepotism. The ratification of the Act should have been the legal basis for prohibiting the practice of nepotism, along with corruption and collusion. But in reality the case of nepotism in Indonesia has never been heard at all despite numerous complaints, statements and evidence.This type of research can be classified in normative juridical research, because this research was conducted by examining secondary data and approaches to the law, this normative study examines the principles of law. Sources of data used are primary data, secondary data, tertiary data, data collection techniques in this study are normative juridical, the data used is literature study.The results of the research conducted by the author are that the regulation of Nepotism is still very weak and the problem of law enforcement institutions authorized to enforce the law against nepotism has not been effective. Therefore to be able to enforce the rules regarding nepotism and to eradicate it, it is necessary to have an effort to reform Law No. 28 of 1999 concerning State Administrators that are Clean, Corruption-Free, Collusion and Nepotism. In addition to improvements in legal arrangements or norms regarding nepotism, cooperation is also needed between law enforcement officials in order to effectively enforce the rule of law regarding nepotism by holding special opinions needed by special investigators to prevent and eradicate the crime of nepotism. And the need for socialization by law enforcement officers to the public about the importance of knowledge of the efforts to prevent and eradicate the crime of nepotism.Keywords: Criminal Acts, Nepotism Regulation, Nepotism, Prohibiting Proof